A political economy of TVET professionalisation: a case study of chefs at a Canadian polytechnic - Loblaw, Timothy J. (2018)
This thesis focuses on a political economy analysis of the relationship between the professional identity and professional development practices of instructors in the postsecondary educational sector of technical and vocational education and training (TVET). My study brings together the concept of the dual-professional identity of postsecondary TVET instructors, the practice of professional development in TVET, and a political economy approach. The research methods adapted for this postgraduate research study were from a qualitative perspective using a case study approach. The case study involved eight culinary instructors, the supervisor of the professional cooking programme, and the director of the hospitality and culinary careers school at a postsecondary polytechnic in Canada, selected using a non-probability sampling technique. My research explored what a political economy analysis would reveal about the relationship between the professional identity and the professional development practices of the culinary instructors/chefs. Throughout this thesis, I use the term, TVET professionalisation, to denote this relationship